Detection of consensus genomic regions and candidate genes for quality traits in barley using QTL meta-analysis - Du, Binbin; Wu, Jindong; Wang, Meng; Wu, Jia; Sun, Chaoyue; Zhang, Xingen; Ren, Xifeng; Wang, Qifei (Frontiers in Plant Science, 2024)
Improving the barley grain quality of barley is a significant objectivemajor goal in barley breeding. In this studyFor this study, a total of 35 papers focusing on quantitative trait loci (QTLs) mapping for barley quality traits published since 2000 were collected.published since 2000 were collected, focusing on the quantitative trait loci (QTLs) mapping for barley quality traits. Among the 454 QTLs identified in these studiesA total of 454 QTLs were collected, 349 of themof which 429 were mapped ontoto high-density consensus maps , which were used for QTL meta-analysisfor QTL meta-analysis. Through QTL meta-analysis, These the initial QTLs were integrated into 42 41 meta-QTLs (MQTLs), with an average confidence interval (CI) of 1.88 66 cM. , which is 88.9% narrower than that of the initial QTLs. Among Remarkably, this CI was 8.22 times narrower than that of the initial QTLs. Out of the 42 41 identified MQTLs identified, 23 25 of them were subsequently validated in publications usinga genome-wide association study (GWAS). From these 23 25 validated MQTLs, 12 ten breeder's MQTLs were selectedscreened out. Synteny analysis comparing barley and wheat MQTLs revealed orthologous relationships between eight breeder's MQTLs and 45 wheat MQTLs. Additionally, 16 17 barley homologs related to rice quality traits were identified within breeder's MQTLs regions by comparative genomics strategiecomparative genomics strategies identified 17 barley homologs associated withrelated to rice quality traits were identified within the regions of the breeder's MQTLs through comparative analysiswithin the breeder's MQTLs regions. These genes are considered potential candidates for controlling quality traits in barley. The findings of this study offer provide valuable insights for molecular marker-assisted breeding and the identification of candidate genes related toassociated with quality traits in barley.